Perancangan Sistem Informasi Penerimaan Siswa Pada SMP PGRI Cikarang Barat Berbasis Web Menggunakan PHP Dan MySQL - Elkin Rilvani (Teknik Informatika, Universitas Pelita Bangsa, 2021)
In a school institution, data processing activities prospective new students is an important part which is often an obstacle in the management and pengarsipannya. On SMP PGRI western Cikarang existing system is still manual, it also resulted in activity requires time and effort is not small. Those problems spurred this research is done by designing a web-based information system. With the web-based information system on SMP PGRI Cikarang Barat, is expected to provide benefits in the data pengelolahan to be more rapid, precise, and accurate. Keywords: Information Systems Admission, SMP PGRI Cikarang Barat, School